Urban governance and electricity losses: An exploration of spatial unevenness in Karachi, Pakistan - NAQVI, Ijlal (Institutional Knowledge at Singapore Management University, 2021)
The inadequate supply of electricity in Pakistan disrupts everyday life and hampers industry and business; in this it is an emblematic indicator of the poor quality of urban governance pervasive in much of the Global South. We focus on the governance of Karachi’s electricity distribution system, and its spatial unevenness across this sprawling metropolis of 15 million residents which encompasses huge informal settlements alongside upscale housing and commercial plazas. Using a dataset with granular, neighborhood-level electricity data, we apply spatial and statistical modeling techniques to understand how transmission and distribution losses, i.e., the utility’s ability to bill for the electricity it supplies, vary across the city. These electricity losses provide a useful lens on the unevenness of urban governance in the city, especially where other sources of detailed socio-economic data are scarce. Our models link losses to higher proportions of residential consumers rather than commercial or industrial. Moreover, based on an analysis of model residuals, we can start to specify the degree to which urban governance is driven by the underlying characteristics of the neighborhood and bring some precision to understanding the spatial distribution of urban governance. Our findings reinforce the importance for governance reforms to be locally situated and informed, while also opening up new possibilities for visualizing electricity governance at a very local level and thus promoting democratic transparency.